An Empirical Evaluation of Generative AI Integration in Instructional Material Development: Its Impact on Teacher Performance and the Moderating Role of Digital Literacy - Muhammad Dhuha Masyhuri; Muhammad Ilham (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: The use of generative artificial intelligence (AI) in education is growing rapidly, particularly in the development of instructional materials. However, research providing an empirical evaluation of its effectiveness on teacher performance—taking digital literacy into account as a readiness factor—remains limited. This study is an evaluative research aimed at assessing the effectiveness of using generative AI in instructional material development on teacher performance, as well as evaluating the moderating role of digital literacy within the framework of educators’ professional accountability. Methodology: This study employs a quantitative approach using an explanatory survey design involving teachers from formal educational institutions in Lhokseumawe City. Data were collected via a Likert-scale questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling (SEM-PLS) through SmartPLS 4 software to evaluate the structural relationships among variables. Main Findings: The analysis results provide evaluative evidence that the use of generative AI significantly contributes to improving teachers’ performance in the aspect of instructional material development. Digital literacy was also found to have a positive and significant effect on performance, with a more dominant influence. However, the evaluation results indicate that digital literacy does not moderate the relationship between the use of generative AI and teacher performance, suggesting that the effectiveness of AI is independent of the level of digital literacy in this sample.    Novelty/Originality of this study: This study contributes to the field of educational evaluation by offering a framework for assessing evidence-based technology integration. The implications for evaluation practice are the need to develop teacher performance assessment standards that include digital technology competencies as part of professional accountability. These results can serve as a policy foundation for educational institutions in evaluating the effectiveness of technology training programs to ensure the adoption of AI that impacts instructional quality.